Magnetic control micro-nano structure surface with silver mirror effect and antifouling property and preparation method of magnetic control micro-nano structure surface

By growing carbonyl iron microcilia and ZnO nanocolumns on the surface of silicon rubber, the problem of difficulty in achieving superhydrophobic and antifouling properties on the surface of silicon rubber is solved, and efficient antifouling effect and silver mirror effect are achieved.

CN119426144APending Publication Date: 2025-02-14CHANGCHUN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411631236.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has limitations when constructing micro-nano multi-stage composite structures on the surface of silicone rubber, and it is difficult to achieve superhydrophobic effects and anti-fouling properties.

Method used

By spraying magnetic fluid in a stable magnetic field, carbonyl iron microcilia are grown on a silicon rubber substrate, and ZnO nanocolumns are grown on its surface by hydrothermal growth method, forming a magnetron micro-nano structure surface with silver mirror effect and antifouling properties. .

Benefits of technology

The superhydrophobic effect and air film adsorption capacity of the silicone rubber surface are achieved, and the antifouling performance is improved. The method is simple to operate, is suitable for large-scale production, and has no toxic side effects on marine organisms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426144A_ABST
    Figure CN119426144A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic control micro-nano structure surface with a silver mirror effect and antifouling performance and a preparation method thereof, and a surface material with a microcilia array is obtained by spraying magnetic fluid onto silicon rubber in a stable magnetic field; then growing ZnO nano-columns on the surface material which is coated with the ZnO crystal seeds and is provided with the micro-cilia array through a hydrothermal growth method; and the super-hydrophobic micro-nano structure surface with the silver mirror effect is obtained. An air film generated by the silver mirror effect is used as a barrier between the material and biological fouling, so that the formation of a surface biological film is prevented, the anti-fouling performance can be effectively improved, and the possibility of further biological pollution is reduced to a great extent. The preparation method and operation are simple, and large-scale preparation and production can be achieved. The physical antifouling manner has no toxic or side effect on other marine organisms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material chemistry, and in particular relates to a magnetically controlled micro-nano structure surface with a silver mirror effect and anti-fouling performance and a preparation method thereof. Background Art

[0003] The marine ecosystem is complex and diverse, with rich flora and fauna, making marine equipment extremely susceptible to biofouling. Therefore, hindering the formation of biofilm on the hull surface can fundamentally and effectively prevent marine organisms from fouling the hull. With the increasing understanding of marine biofouling, the technology of hindering the formation of biofilm on the surface of materials has also been rapidly developed. Chemical antifouling methods usually have varying degrees of toxicity to marine organisms or have other effects on their metabolism. For example, SeaNine-211 is a commonly used antifouling agent, the main ingredient of which is 4,5-dichloro-2-n-octyl-4-isothiazoline-3-one (DCOIT), which is a broad-spectrum fungicide. When used as a marine antifouling agent, it usually has toxic effects on many non-target organisms and poses a hazard to their brains, livers, plasma and gonads.

[0004] On the contrary, many organisms in nature exhibit different surface wettability due to their special surface micro-nano structures, thus having anti-fouling properties and the ability to resist marine biofouling. The superhydrophobic properties of solid surfaces are determined by both the solid surface free energy and the roughness. Superhydrophobic surfaces can be achieved in two ways: 1) constructing a micro-nano multi-level composite structure on the solid surface to increase the surface roughness; 2) modifying the solid surface with a micro-nano multi-level composite structure with a low surface energy substance to reduce the surface energy of the material. At present, the methods for constructing micro-nano multi-level composite structures on solid surfaces include: sol-gel method, plasma method, electrospinning method, physical or chemical vapor deposition method, template method, electrochemical method, and phase separation method. In recent years, many researchers have used the above methods to construct rough surfaces on different substrates (such as glass, silicon wafers, and metals) and achieved superhydrophobic effects. However, the above methods have certain limitations in the application of silicone rubber, which is mainly due to the poor chemical resistance and physical and mechanical properties of silicone rubber. How to simply and effectively construct a micro-nano multi-level composite structure on the surface of silicone rubber so that silicone rubber can achieve superhydrophobicity and have air film adsorption and antifouling properties has become a research hotspot in the antifouling field. Summary of the invention

[0006] The purpose of the present invention is to provide a magnetically controlled micro-nanostructure surface with a silver mirror effect and anti-fouling performance, which exhibits super-hydrophobic properties by virtue of its unique physical morphology and structure, and to provide a preparation method which is simple and universal.

[0007] The present invention provides the following technical solution: first, a surface material with a microciliary array is obtained by spraying a magnetic fluid onto a substrate in a stable magnetic field. Subsequently, ZnO nanocolumns are grown on the surface material with a microciliary array coated with ZnO crystal seeds by a hydrothermal growth method, thereby obtaining a magnetically controlled micro-nanostructure surface with a silver mirror effect and antifouling properties.

[0008] A method for preparing a magnetically controlled micro-nanostructure surface having a silver mirror effect and anti-fouling properties, the specific steps are as follows: Step 1: preparing a silicone rubber substrate; Step 2: growing carbonyl iron microcili on the surface of silicone rubber substrate; Step 3: coating ZnO crystal seeds on the surface of carbonyl iron microcili; Step 4: Grow ZnO nanocolumns on the surface of carbonyl iron microciliary hairs coated with ZnO crystal seeds to obtain a magnetically controlled micro-nanostructure surface with silver mirror effect and anti-fouling properties.

[0009] In step 1, the steps of preparing the silicone rubber substrate are as follows: Weigh 22.97g of room temperature vulcanized silicone rubber and 0.30g of curing agent, stir evenly with a mechanical stirrer at 2000 rpm, and place in a vacuum box to eliminate bubbles. After the mixture is free of bubbles, take it out and pour it into the acrylic tank with the template. After standing for a while, cover it with an acrylic cover plate, press it with a heavy object, and cure it for 24 hours to obtain a silicone rubber substrate.

[0010] In step 2, the steps of growing carbonyl iron microcili on the surface of the silicone rubber substrate are as follows: 1) Add 5 g of silicone rubber to 10 g of ethyl acetate and stir evenly; then, add 6 g of carbonyl iron powder and 0.1 g of curing agent into the solution, and then perform ultrasonic dispersion for 20 minutes to obtain a magnetic fluid; 2) Spray the magnetic fluid onto the substrate and place a magnet at the bottom of the substrate with a magnetic field strength of 350 mT; after curing, carbonyl iron microciliary hairs grow on the surface of the silicone rubber substrate; In step 3, the steps of coating ZnO crystal seeds on the surface of carbonyl iron microciliary hairs are as follows: 1) dissolving a solution containing 30 mM sodium hydroxide and 20 mM zinc acetate in 50 mL of ethanol, and stirring the mixture at 60 °C for 2 hours to obtain a ZnO crystal seed solution; 2) Immerse the surface material with the microciliary array in the seed solution at room temperature for 30 seconds to ensure that the ZnO crystal seeds are fully covered on its surface, and then dry it at 90°C for 30 minutes; In step 4, the steps of growing ZnO nanocolumns on the surface of carbonyl iron microciliary hairs coated with ZnO crystal seeds are as follows: 60 mM zinc acetate and 60 mM hexamethylenetetramine solution were dissolved in 50 mL deionized water and transferred to a 50 mL Teflon-lined stainless steel reactor. The ZnO seed-coated surface material with a microciliary array was then immersed in the mixture and heated at 90 °C for 6 h, washed three times with deionized water, and dried at 45 °C to obtain a magnetically controlled micro-nanostructure surface with a silver mirror effect and antifouling properties.

[0011] Preferably, a spray-wait-spray cycle is adopted when spraying the magnetic fluid in step 2.

[0012] Beneficial effects of the present invention: In the present invention, microcilia and ZnO nanocolumns are grown on the surface of silicone rubber to provide the surface of silicone rubber with a micro-nano structure, thereby achieving a super-hydrophobic effect; In the present invention, a surface material with a microciliary array is obtained by spraying a magnetic fluid onto silicone rubber in a stable magnetic field; In the present invention, ZnO nanocolumns are grown on a surface material having a microciliary array coated with ZnO crystal seeds by a hydrothermal growth method; The super-hydrophobic micro-nano surface obtained by the present invention has air film adsorption capability, which hinders the formation of biofilm on its surface and improves the anti-fouling capability; The preparation method of the present invention is simple to operate and can realize large-scale preparation and production; The invention uses physical antifouling method and has no toxic side effects on other marine organisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a scanning electron microscope image of the SR-CIPs-ZnO surface of the present invention.

[0014] Figure 2 This is a scanning electron microscope image of the SR-CIPs-ZnO surface of the present invention.

[0015] Figure 3 The scanning electron microscope image and elemental analysis diagram of the SR-CIPs-ZnO surface of the present invention.

[0016] Figure 4 These are the water contact angle diagrams of SR, SR-CIPs and SR-CIPs-ZnO prepared in the present invention.

[0017] Figure 5 This is a diagram of the underwater silver mirror effect of SR, SR-CIPs and SR-CIPs-ZnO prepared by the present invention.

[0018] Figure 6 This is an antifouling experimental diagram of SR, SR-CIPs and SR-CIPs-ZnO prepared in the present invention in the Bacillus subtilis attachment experiment.

[0019] Figure 7 Ultra-depth three-dimensional microscope images of Bacillus subtilis on the surfaces of SR, SR-CIPs and SR-CIPs-ZnO prepared in the present invention.

[0020] Figure 8 This is a plate colony count diagram of the eluate of SR, SR-CIPs and SR-CIPs-ZnO prepared in the present invention in the Bacillus subtilis attachment experiment.

[0021] Fig. 9 This is an antifouling experiment diagram of the eluate of SR, SR-CIPs and SR-CIPs-ZnO prepared in the present invention in the Chlorella attachment experiment.

[0022] Fig.10 This is a super-depth three-dimensional microscope image of Chlorella attached to the surfaces of SR, SR-CIPs and SR-CIPs-ZnO prepared in the present invention. DETAILED DESCRIPTION

[0023] Example 1 (Preparation of Silicone Rubber Substrate-SR) Weigh 22.97g of room temperature vulcanized silicone rubber and 0.30g of curing agent, stir evenly with a mechanical stirrer at 2000 rpm, and place in a vacuum box to eliminate bubbles. Take out the mixture after there are no bubbles, pour it into the acrylic template groove, let it stand for a while, cover it with an acrylic cover plate, press it with a heavy object, and cure it for 24 hours to obtain a silicone rubber substrate.

[0024] Example 2 (SR-CIPs) 5 g of silicone rubber was added to 10 g of ethyl acetate and magnetically stirred for 20 minutes to ensure that the silicone rubber was evenly dispersed in the ethyl acetate solution; subsequently, 6 g of carbonyl iron powder and 0.1 g of curing agent were added to the solution, and then ultrasonic dispersion was performed for 20 minutes to obtain a magnetic fluid; then, the magnetic fluid was sprayed onto the substrate using a spray gun, and a magnet was placed at the bottom. During the spraying process, the magnetic fluid was stabilized after each spraying and then sprayed again, i.e., a spray-wait-spray cycle; after standing and curing for 12 hours, microcilia grew on the smooth surface of the silicone rubber to obtain SR-CIPs.

[0025] Example 3 (SR-CIPs-ZnO) A solution containing 30 mM sodium hydroxide and 20 mM zinc acetate was dissolved in 50 mL of ethanol, and the mixture was stirred at 60 ° C for 2 hours to obtain a ZnO crystal seed solution; then the SR-CIPs were immersed in the seed solution at room temperature for 30 seconds to ensure that the ZnO crystal seeds were fully covered on its surface, and then dried at 90 ° C for 30 minutes; then, 60 mM zinc acetate and 60 mM hexamethylenetetramine solution were dissolved in 50 mL of deionized water and transferred to a 50 mL Teflon-lined stainless steel reactor, and then the ZnO seed-coated SR-CIPs were immersed in the mixture and heated at 90 ° C for 6 hours; the resulting surface-grown ZnO nanopillar microciliary array composite material was washed 3 times with deionized water and dried at 45 ° C. SR-CIPs-ZnO was obtained.

[0026] Effect verification like Figure 1 As shown, by observing the SR-CIPs-ZnO surface using a scanning electron microscope, it can be seen that microcilia have successfully grown on the SR-CIPs-ZnO surface.

[0027] like Figure 2 As shown, the surface of SR-CIPs-ZnO was observed using a scanning electron microscope, and it can be seen that ZnO nanorods were successfully grown on the surface of SR-CIPs-ZnO.

[0028] like Figure 3 As shown, scanning electron microscopy and elemental analysis diagrams indicate that carbonyl iron powder and ZnO nanorods are successfully loaded on the surface of silicone rubber.

[0029] like Figure 4 As shown, the water contact angle test results indicate that SR-CIPs-ZnO reaches a superhydrophobic state, while the water contact angles of SR-CIPs and SR do not reach a superhydrophobic state.

[0030] like Figure 5 As shown, compared with SR-CIPs and SR, the SR-CIPs-ZnO surface can adsorb air film.

[0031] Bacillus subtilis attachment experiment: SR, SR-CIPs, and SR-CIPs-ZnO were immersed in artificial seawater and incubated with Bacillus subtilis suspension for dynamic antifouling testing. Bacillus subtilis suspension accounting for 1.3% of the volume of artificial seawater was incubated with the samples for 6 hours, 12 hours, and 24 hours. Subsequently, the samples were gently rinsed with PBS to eliminate non-adherent Bacillus subtilis. Each sample was then placed in 30 mL of PBS and sonicated for 1 minute to elute the adherent Bacillus subtilis. The optical density (OD) at 600 nm was measured. 600nm) to determine the Bacillus subtilis adhesion concentration of all samples. In addition, the Bacillus subtilis eluate was cultured on LB solid medium at 37°C for 12 hours, and then the colonies were counted. In addition, the samples were observed under an ultra-depth 3D microscope to evaluate the number of Bacillus subtilis adhered to the surface.

[0032] like Figure 6 As shown in the figure, at three different time periods, the OD of SR-CIPs-ZnO was compared with that of SR-CIPs and SR. 600nm Both are smaller than the OD of SR-CIPs and SR 600nm , so the number of Bacillus subtilis attached to SR-CIPs-ZnO is the least.

[0033] like Figure 7 As shown, the images of ultra-depth 3D microscopy proved that the amount of Bacillus subtilis attached to the surface of SR-CIPs-ZnO was the least compared with SR-CIPs and SR.

[0034] like Figure 8 As shown, the plate colony counting results showed that the amount of bacteria in the eluate of the SR-CIPs-ZnO sample was less than the amount of Bacillus subtilis in the eluate of the SR-CIPs and SR samples.

[0035] Chlorella attachment experiment: The samples were incubated with a suspension of Chlorella for 6, 12, and 24 hours in artificial seawater containing 1.3% of the suspension. Images of the number of bacteria adhering to the surface were observed using a super-depth 3D microscope. In addition, OD 680nm Measurements were made to quantitatively assess the density of Chlorella attached to the samples.

[0036] like Fig. 9 As shown in the figure, at three different time periods, the OD of SR-CIPs-ZnO was compared with that of SR-CIPs and SR. 680nm Both are smaller than the OD of SR-CIPs and SR 680nm , so the amount of Chlorella attached to SR-CIPs-ZnO is the least.

[0037] like Fig.10 As shown, the images of ultra-depth 3D microscopy proved that the amount of Chlorella attached to the surface of SR-CIPs-ZnO was the least compared with SR-CIPs and SR.

[0038] The above experimental results show that the surface of SR-CIPs-ZnO has a micro-nano structure; SR-CIPs-ZnO has reached a superhydrophobic state; SR-CIPs-ZnO adsorbed an air film within 12 hours; in the antifouling experiment, compared with the other two groups of samples, SR-CIPs-ZnO showed the lowest adhesion ability of Bacillus subtilis and Chlorella, demonstrating its excellent antifouling ability.

[0039] Matters not covered by the present invention are known technologies.

[0040] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. For technical workers in this technical field, changes or substitutions that can be easily conceived are also considered as the protection scope of the present invention.

Claims

1. A method for preparing a magnetically controlled micro-nanostructure surface having a silver mirror effect and antifouling properties, characterized in that: The specific steps are as follows: Step 1: preparing a silicone rubber substrate; Step 2: growing carbonyl iron microcili on the surface of silicone rubber substrate; Step 3: coating ZnO crystal seeds on the surface of carbonyl iron microcili; Step 4: Grow ZnO nanocolumns on the surface of carbonyl iron microciliary hairs coated with ZnO crystal seeds to obtain a magnetically controlled micro-nanostructure surface with silver mirror effect and anti-fouling properties.

2. The method for preparing a magnetically controlled micro-nanostructure surface having a silver mirror effect and antifouling properties according to claim 1, characterized in that: In step 1, the steps of preparing the silicone rubber substrate are as follows: Weigh 22.97g of room temperature vulcanized silicone rubber and 0.30g of curing agent, stir evenly with a mechanical stirrer at 2000 rpm, and place in a vacuum box to eliminate bubbles; After the mixture has no bubbles, take it out and pour it into the acrylic template groove. After standing for a while, cover it with an acrylic cover plate and press it with a heavy object to cure for 24 hours to obtain a silicone rubber substrate.

3. The method for preparing a magnetically controlled micro-nanostructure surface having a silver mirror effect and antifouling properties according to claim 1, characterized in that: In step 2, the steps of growing carbonyl iron microcili on the surface of the silicone rubber substrate are as follows: 1) Add 5 g of silicone rubber to 10 g of ethyl acetate and stir evenly; then, add 6 g of carbonyl iron powder and 0.1 g of curing agent into the solution, and then perform ultrasonic dispersion for 20 minutes to obtain a magnetic fluid; 2) Spray the magnetic fluid onto the substrate and place a magnet at the bottom of the substrate with a magnetic field strength of 350 mT; after curing, carbonyl iron microcili grow on the surface of the silicone rubber substrate.

4. The method for preparing a magnetically controlled micro-nanostructure surface having a silver mirror effect and antifouling properties according to claim 1, characterized in that: In step 3, the steps of coating ZnO crystal seeds on the surface of carbonyl iron microciliary hairs are as follows: 1) dissolving a solution containing 30 mM sodium hydroxide and 20 mM zinc acetate in 50 mL of ethanol, and stirring the mixture at 60 °C for 2 hours to obtain a ZnO crystal seed solution; 2) The surface material with the microciliary array was immersed in the seed solution for 30 seconds at room temperature to ensure that the ZnO crystal seeds were fully covered on its surface, and then dried at 90 °C for 30 minutes.

5. The method for preparing a magnetically controlled micro-nanostructure surface having a silver mirror effect and antifouling properties according to claim 1, characterized in that: In step 4, the steps of growing ZnO nanocolumns on the surface of carbonyl iron microciliary hairs coated with ZnO crystal seeds are as follows: 60 mM zinc acetate and 60 mM hexamethylenetetramine solution were dissolved in 50 mL deionized water and transferred to a 50 mL Teflon-lined stainless steel reactor. The ZnO seed-coated surface material with a microciliary array was then immersed in the mixture and heated at 90 °C for 6 h, washed three times with deionized water, and dried at 45 °C to obtain a magnetically controlled micro-nanostructure surface with a silver mirror effect and antifouling properties.

6. The method for preparing a magnetically controlled micro-nanostructure surface having a silver mirror effect and antifouling properties according to claim 3, characterized in that: When spraying the magnetic fluid in step 2, a spray-wait-spray cycle is adopted.

7. A magnetically controlled micro-nanostructure surface having a silver mirror effect and anti-fouling properties, prepared by the preparation method according to any one of claims 1 to 6.